Case Series: Gene Expression Analysis in Canine Vogt-Koyanagi-Harada/Uveodermatologic Syndrome and Vitiligo Reveals Conserved Immunopathogenesis Pathways Between Dog and Human Autoimmune Pigmentary Disorders - Egbeto, Ista A.; Garelli, Colton J.; Piedra-Mora, Cesar; Wong, Neil B.; David, Clement N.; Robinson, Nicholas A.; Richmond, Jillian M. (Frontiers in Immunology, 2020)
Vogt-Koyanagi-Harada syndrome (VKH) and vitiligo are autoimmune diseases that target melanocytes. VKH affects several organs such as the skin, hair follicle, eyes, ears, and meninges, whereas vitiligo is often limited to the skin and mucosa. Many studies have identified immune genes, pathways and cells that drive the pathogeneses of VKH and vitiligo, including interleukins, chemokines, cytotoxic T-cells, and other leukocytes. Here, we present case studies of 2 canines with VKH and 1 with vitiligo, which occurred spontaneously in client-owned companion dogs. We performed comparative transcriptomics and immunohistochemistry studies on lesional skin biopsies from these cases in order to determine if the immunopathogenesis of autoimmune responses against melanocytes are conserved. In dogs, we found enrichment of T cell gene signatures, with upregulation of IFNG, TNF, PRF1, IL15, CTSW, CXCL10 and CCL5 in both VKH and vitiligo in dogs compared to healthy controls. Similar findings were reported in humans, suggesting that these genes play a role in the pathogenesis of spontaneous VKH and vitiligo. T cell-associated genes, including FOXP3 and TBX21, were enriched, while IGFBP5, FOXO1 and PECAM1 were decreased compared to healthy controls. Further, we identified TGFB3, SFRP2, and CXCL7 as additional potential drivers of autoimmune pigmentary disorders. Future studies exploring the immunopathogenesis of spontaneous autoimmunity will expand our understanding of these disorders, and will be useful in developing targeted therapies, repurposing drugs for veterinary and human medicine, and predicting disease prognosis and treatment response.